A categorização e a validação das respostas abertas em surveys políticos - HENKEL, Karl (Universidade Federal do Pará, 2019)
The article deals with the problem of the categorization of answers about politics, government, and democracy obtained through open-ended questions in a survey with a random sample of 800 interviewees. In order to identify the degree of comprehensibility of the questions, a pre-test and missing value analysis were carried out to elaborate a psychometric profile. In the categorization process, the deductive method was superior to the inductive one. The media and the life cycle position influences perception about politics and government. The validation of intra- and inter-coder reliability shows that coders, at a given moment, begin to accept irrational responses as rational ones, and that they can be subject to framing effects.